2016
DOI: 10.1590/0103-6440201600337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apical Preparation Size and Working Length on Debris Extrusion

Abstract: The aim of this study was to quantitatively evaluate the amount of apically extruded debris by single-file reciprocating instruments with different working lengths and apical preparation sizes. Eighty human single-rooted mandibular incisors were used and conventional access cavities were prepared. Then, the specimens were divided into four groups (n=20), according to root canal instrumentation: Reciproc size 25, .08 taper and Reciproc size 40, .06 taper instruments were used at the foramen; Reciproc size 25, .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 24 publications
0
48
0
7
Order By: Relevance
“…Another clinically relevant aspect of these instruments/kinematics is their greater tendency to extrude debris through the apical foramen (AF) during the mechanical preparation of the root canal system, which can lead to postoperative pain 5 , 23 . This finding is not unanimous in the literature; however, it seems to be related to the design of the instruments (larger or smaller area for debris accumulation between the coils) and kinematics (release of the scrapings collected when the direction of movement is reversed) 1 , 3 , 17 , 21 .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Another clinically relevant aspect of these instruments/kinematics is their greater tendency to extrude debris through the apical foramen (AF) during the mechanical preparation of the root canal system, which can lead to postoperative pain 5 , 23 . This finding is not unanimous in the literature; however, it seems to be related to the design of the instruments (larger or smaller area for debris accumulation between the coils) and kinematics (release of the scrapings collected when the direction of movement is reversed) 1 , 3 , 17 , 21 .…”
Section: Introductionmentioning
confidence: 74%
“…Regarding the definition of the apical limit of instrumentation, Endodontics has been dedicated to investigating possible variations, and understanding the need to disinfect the entire root canal system, not only to a historically predetermined limit (i.e., 1.0 mm short of the AF), but throughout its entire extension, which means right up to the AF. Thus, apical limits considering the root canal length (RCL) of the tooth, or even beyond this, as being an ideal apical stop have appeared in the literature 17 , 19 , 25 . Although not consolidated, this practice could allow irrigation in the apical region and promote a more efficient mechanical debridement of the apical portion, including the AF, optimizing the disinfection of the root canal and favouring its repair 14 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Ni and Ti particles could apically be extruded to the periapical tissues and their consequences still remains unclear. Several papers have reported that dentin chips, microrganisms and their by-products, pulp tissue and irrigants may extrude to the periapical tissues during canal preparation (Mittal, Singla, Garg, & Dhawan, 2015;Silva et al, 2016;Uzunoglu, Turker, & G€ orduysus, 2015). Apical extrusion of debris may lead to postoperative symptoms and impair the treatment outcome (Silva et al, 2016 (Shen, Haapasalo, Cheung, & Peng, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Many variables may influence the occurrence of more or less apical extrusion of debris, such as root canal curvature, anatomic variations, patency approach, working length, increased apical preparation size, number of instruments used, and movement kinematics during instrumentation. 1,11,12 However, with the development of different designs and heat treatments for nickel-titanium alloys and their consequent superelasticity, faster access to the foramen, and possible foraminal enlargement became important factors to be considered in the amount of debris that can be apically extruded. 13 With the introduction of different reciprocating single-file instrumentation systems, it is important to analyze the behavior of these instruments during root canal preparation, and an aspect lacking scientific evidence is the amount of extruded debris.…”
Section: Introductionmentioning
confidence: 99%